IDENTIFIKASI JALUR PATAHAN DENGAN METODE GEOLISTRIK HAMBATAN JENIS DI WILAYAH PALU BARAT - Fitriani, Zelly Rizky; Rusydi H., Muhammad; Th Musa, Moh. Dahlan (Univ. Tadulako, 2012)
Research identify fault lines with resistivity geoelectric measurements in West Palu has been done. This study aimed to determine the geological structure, and also the type of rock layers below the surface area of research. This measurement was carried out in two areas in the western district of Palu, the Kalora and Kabonena, using geoelectric methods resistance type with Wenner configuration. Data processing was done using software EarthImager 2D. From the results of treatment, obtained a description of the geological structure in line 2 at Kalora areas there resistance values between 1212-6000 ohm-m which allegedly was granite layer that separated by a layer of sandy loam with a resistance value of 200-1000 ohm-m in coordinates of 119 °49'33,7? BT and 00 ° 52'42, 5